Autosomal recessive hypophosphatemic rickets type 2; a novel mutation in the ENPP1 gene - Bitkin, Eda Çelebi; Aymelek, Huri Sema (The Turkish Journal of Pediatrics, 2022)
Background. Hypophosphatemic rickets (HR) is a rare disease caused by several genetic mutations in factors that cause an increase in fibroblast growth factor 23 (FGF23), and renal phosphate transporters. ENPP1 (ectonucleotide pyrophosphatase / phosphodiesterase 1) mutations cause autosomal recessive inheritance hypophosphatemic rickets type 2. Case. In our study, we present a novel mutation in the ENPP1 gene detected in 4 siblings in a single family. Conclusion. Our findings can be applied to further understand molecular pathogenesis and to establish a correlation between genotype and phenotype for HR.